Differential Gene Expression in Bladder Tumors from Workers Occupationally Exposed to Arylamines - Ramya T. Kolli (Hindawi Limited, 2021)
Occupational exposure to the arylamines benzidine and β-naphthylamine increase bladder cancer risk up to 100-fold, making them some of the most powerful human carcinogens. We hypothesize that tumors arising in people with occupational exposures have different patterns of gene expression than histologically similar tumors from people without such exposures. In a case-case study, we compare gene expression in 22 formalin-fixed paraffin-embedded (FFPE) bladder tumors from men with high-level occupational exposure to arylamines to that in 26 FFPE bladder tumors from men without such exposure. Gene expression analysis was performed on the NanoString nCounter system using a PanCancer Progression Panel comprised of 740 cancer progression-related genes and a custom panel of 69 arylamine- and bladder cancer-related genes which were chosen from in vitro studies. Although fold differences were small, there was evidence of differential expression by exposure status for 17 genes from the Progression Panel and 4 genes from the custom panel. In total, 10 genes showed dose-response association at a p<0.01, of which 4 genes (CD46, NR4A1, BAX, and YWHAZ) passed a false discovery rate (FDR) q value cutoff of 0.05 but were not significant after Bonferroni correction. Overall, we find limited evidence for differentially expressed genes in pathways related to DNA damage signaling and epithelial-to-mesenchymal transition (EMT).